Penataan Kawasan Wisata Arena Pacu Jalur Di Kuantan Singingi - Metior, Rizki; Aldy, Pedia; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Pacu Jalur tourism is a ethnic tour owned by Kuantan Singingi Regency. Historically Pacu Jalur itself means to unite all the people of Kuantan Singingi with compactness. But it is still not yet optimally in terms of facilities and containers to perform this particular culture, in order to give the impression as well as the meaning and able to entertain as a tourism area. Moving on from the problems, expected the arrangement of tourism area is to be a real solution to support the infrastructure of existing ethnic tour in Kuantan Singingi. The reason of the title above is not maximal utilization of tourism area Pacu Jalur which is a tourism icon of Kuantan Singingi Regency, causing a lack of infrastructure and public understanding of the Pacu Jalur. Reason of traditional architecture theme to increase tourism potential and well communicate about Pacu Jalur through traditional character of Godang House. To realize the concept that in the arrangement is Symbiosis of History and the Present and Symbiosis of Tradition and Modern Architecture, which connects to between the characters of Godang Houses, Pacu Jalur and tourist activity to the Arrangement of Tourism Area Arena Pacu Jalur in Kuantan Singingi. Referring to the RDTR Teluk Kuantan city, the purpose is to optimized the Arrangement of Tourism Area Pacu Jalur, demonstrating cultural activities and public activities and facilitated by the form of the cottage 's accommodation.Keywords: Arrangement of Tourism Area, Pacu Jalur Kuantan Singingi, Godang House Architecture, Symbiosis of History and Present, Symbiosis of Tradition and Modern Architecture.